Virtual Reality Technology: An Essential Way of Remediation for Luoshan Shadow Puppet - Taotao, Xu; Musdi, Shanat; Jian, Chen; Bingqian, Zhou; Qiujin, Zhao (Akademia Baru, 2026)
Virtual reality (VR) technology offers a promising avenue for enhancing the remediation of Luoshan shadow puppets, providing a richer and more immersive viewing experience, that supports the preservation of traditional cultural heritage and expands educational and promotional opportunities. This paper analyzes the remediation process of Luoshan shadow puppets through the lens of modern communication and innovative proposes a remediation strategy based on virtual reality technology (VR). This strategy leverages fundamental principles of computer image processing, using a simulation platform to simulate, digitize, visualize, and interpret this traditional shadow art form. The study explores a VR-driven approach to remediating Luoshan shadow puppets, assessing current communication, practices, analyzing remediation characteristics, and roposing a specific VR-based methods. The findings highlight significant challenges in the remediation process, noting the rarity of VR applications for Luoshan shadow puppets and facing obstacles such as technical complexity, cost considerations, cultural adaptation, and user acceptance. Despite these challenges, the study underscores the crucial role of VR technology in the remediation of Luoshan shadow puppets, facilitating innovative performance forms, enhancing interactivity, and enabling digital preservation and communication efforts. Ultimately, the research demonstrates that VR-based remediation methods can introduce new creative possibilities and innovative elements for folklore artists as well as designers who preserve and revitalise cultural heritage.